The All-Alpha Domains of Coupling Proteins from the Agrobacterium tumefaciens VirB/VirD4 and Enterococcus faecalis pCF10-Encoded Type IV Secretion Systems Confer Specificity to Binding of Cognate DNA Substrates - Whitaker, Neal (J Bacteriol, 2015)
Bacterial type IV coupling proteins (T4CPs) bind and mediate the delivery of DNA substrates through associated type IV secretion systems (T4SSs). T4CPs consist of a transmembrane domain, a conserved nucleotide-binding domain (NBD), and a sequence-variable helical bundle called the all-alpha domain (AAD). In the T4CP structural prototype, plasmid R388-encoded TrwB, the NBD assembles as a homohexamer resembling RecA and DNA ring helicases, and the AAD, which sits at the channel entrance of the homohexamer, is structurally similar to N-terminal domain 1 of recombinase XerD. Here, we defined the contributions of AADs from the Agrobacterium tumefaciens VirD4 and Enterococcus faecalis PcfC T4CPs to DNA substrate binding. AAD deletions abolished DNA transfer, whereas production of the AAD in otherwise wild-type donor strains diminished the transfer of cognate but not heterologous substrates. Reciprocal swaps of AADs between PcfC and VirD4 abolished the transfer of cognate DNA substrates, although strikingly, the VirD4-AAD(PcfC) chimera (VirD4 with the PcfC AAD) supported the transfer of a mobilizable plasmid. Purified AADs from both T4CPs bound DNA substrates without sequence preference but specifically bound cognate processing proteins required for cleavage at origin-of-transfer sequences. The soluble domains of VirD4 and PcfC lacking their AADs neither exerted negative dominance in vivo nor specifically bound cognate processing proteins in vitro. Our findings support a model in which the T4CP AADs contribute to DNA substrate selection through binding of associated processing proteins. Furthermore, MOBQ plasmids have evolved a docking mechanism that bypasses the AAD substrate discrimination checkpoint, which might account for their capacity to promiscuously transfer through many different T4SSs. IMPORTANCE For conjugative transfer of mobile DNA elements, members of the VirD4/TraG/TrwB receptor superfamily bind cognate DNA substrates through mechanisms that are largely undefined. Here, we supply genetic and biochemical evidence that a helical bundle, designated the all-alpha domain (AAD), of T4SS receptors functions as a substrate specificity determinant. We show that AADs from two substrate receptors, Agrobacterium tumefaciens VirD4 and Enterococcus faecalis PcfC, bind DNA without sequence or strand preference but specifically bind the cognate relaxases responsible for nicking and piloting the transferred strand through the T4SS. We propose that interactions of receptor AADs with DNA-processing factors constitute a basis for selective coupling of mobile DNA elements with type IV secretion channels.